Advances in Electrocatalytic N2 Reduction—Strategies to Tackle the Selectivity Challenge. Issue 6 (26th October 2018) - Chen, Gao‐Feng; Ren, Shiyu; Zhang, Lili; Cheng, Hui; Luo, Yaru; Zhu, Kehan; Ding, Liang‐Xin; Wang, Haihui
Abstract: The industrial process used to reduce N2 to NH3, typically the Haber–Bosch process, is energy‐intensive and highly dependent on fossil fuels, a major source of greenhouse gas emissions causing undesirable climate change. Electrochemical reduction of N2 to NH3 using renewable energy is one attractive approach to address this problem. A major challenge for electrochemical nitrogen reduction reaction (NRR) is low catalytic activity, accompanied by ultralow selectivity. Current studies have made some breakthroughs in Faradaic efficiency, with reasonable current density, while remaining far from satisfying the needs of commercial applications. This review discusses current strategies, focusing on the perspectives of catalyst design, cell configuration, electrolyte choice, etc., to tackle the selectivity challenge. In addition, rigorous control experiments to eliminate possible ammonia contamination and standard ammonia detection methods to ensure data accuracy are proposed, providing guidance for the field of NRR studies. Abstract : This review summarizes current strategies for tackling the selectivity challenge of electrocatalytic nitrogen reduction reaction (NRR). The proposed strategies from the perspectives of catalyst design, cell configuration, electrolyte choice, etc., are systematically researched. To ensure experimental rigor, a standard pattern for executing control experiments is recommended. This review is expected to motivate the NRR field toward greater advancement.